Perbedaan Pola Channeling dan Executing pada Pembiayaan Linkage Program di Bank Syariah Mandiri Cabang Salatiga - Febri Antika Sonya Harum Dapta (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
The purpose of the research was to determine the procedures and schemesof executing and channeling system of Linkage Program in Syariah MandiriBank Branch Salatiga, and to know the difference between the two systems.The method I used is descriptive qualitative method. The results of thisstudy concluded that procedures and schemes of executing and channelingsystem different, the difference lies in the role of Linkage in the process offiling financing. While other differences largely lies in who their customers,the role of the Linkage institution, information about the end user, the viewprocedures in terms of end-user, provisions Debt to Equity Ratio (DER) ofeach system, financing decisions of end user, end user guarantees storage,document storage end user financing, and the type of contract used. Ofthese differences, when viewed from the perspective of end users, a muchmore easier and simpler to implement is executing system, the system istherefore more desirable